Spun-bonded non-woven fabric, method for producing same, laminated non-woven fabric, and sanitary material and clothing using same
By using organic peroxide as crystallization nucleating agent in spunbond nonwoven fabrics and controlling the branching degree of fibers, the contradiction between fiber strength and flexibility is solved, and the high flexibility and excellent mechanical properties of spunbond nonwoven fabrics are achieved, which is suitable for high-order processing.
Patent Information
- Application Number
- CN202380064787.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-08-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-08-31
AI Technical Summary
When the existing spunbond nonwoven fabrics improve their softness, the fiber strength decreases, resulting in deterioration of mechanical properties, making it difficult to perform wrinkle processing and high-order processing.
By remaining a certain amount of organic peroxide in the spunbond nonwoven fabric as crystallization nucleating agent, and controlling the branching degree of fibers within a specific range, the molecular orientation of the fibers is improved, thereby improving the strength and mechanical properties of the fibers.
The high flexibility and excellent mechanical properties of spunbond nonwoven fabrics are achieved, and high-order processing such as wrinkle processing and jointing with other components can be easily performed.
Smart Images

Figure BDA0005302552700000151 
Figure BDA0005302552700000331 
Figure BDA0005302552700000361
Abstract
Description
Technical Field
[0001] The present invention relates to a spunbonded nonwoven fabric having not only softness but also excellent mechanical properties and high processability, a method for producing the same, and sanitary materials and clothing using the same. Background Art
[0002] Spunbonded nonwoven fabrics made of polyolefins, particularly polypropylene spunbonded nonwoven fabrics, are widely used, mainly for sanitary material applications, because of their low cost and excellent processability.
[0003] In recent years, polypropylene spunbond nonwoven fabrics used for sanitary materials have been required to have further improved softness, and several proposals have been made so far to achieve this goal.
[0004] For example, Patent Document 1 proposes a nonwoven web of fine fibers formed from treated particles of a polymer having a specific molecular weight distribution and a melt flow rate of a certain level or higher.
[0005] In addition, Patent Document 2 proposes a method for producing a nonwoven fabric, wherein a propylene polymer and an organic peroxide are supplied to an extruder (the extruder is provided with a cross-cutting saw and a Unimelt screw), a propylene polymer resin composition containing the propylene polymer and the organic peroxide in the extruder is melt-kneaded, and the melt-kneaded propylene polymer resin composition is spun to produce a nonwoven fabric. Furthermore, it is described that according to such a method for producing a nonwoven fabric, it is possible to suppress yarn breakage and to obtain a nonwoven fabric having excellent spinnability.
[0006] Furthermore, Patent Document 3 proposes a polypropylene resin composition containing an organic peroxide, characterized in that a certain amount of organic peroxide is added to a propylene / α-olefin random copolymer having certain characteristics polymerized by a metallocene catalyst, and the ratio of the melt flow rate of the resin composition to the melt flow rate of the resin composition after vacuum constant temperature drying is less than a certain value. Furthermore, it is described that such a resin composition can be used as a useful resin composition capable of adjusting melt viscosity during molding processing by using it alone or in combination with other polypropylene resins in the form of a masterbatch.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 7-119014
[0010] Patent Document 2: Japanese Patent No. 6599078
[0011] Patent Document 3: Japanese Patent Application Publication No. 2003-138075 Summary of the invention
[0012] Problems to be solved by the invention
[0013] Patent document 1 states that: According to the technology, the polymer is treated in a manner that narrows the molecular weight distribution and reduces the molecular weight of the polymer (i.e., increases the melt flow rate), and as a result, the nonwoven web of the invention can be efficiently manufactured by a melt-blown method. However, by adjusting the melt flow rate to a low level, when a spunbonded nonwoven fabric is to be obtained, there are the following problems, namely, the fiber strength will be reduced, the mechanical properties of the nonwoven fabric will be greatly reduced, and it will be difficult to perform high-order processing such as pleating and joining with other components, and the mechanical properties of the final product itself will deteriorate.
[0014] In addition, in the technologies proposed in Patent Documents 2 and 3, although the spinnability can be improved to some extent by increasing the melt flow rate of the resin, the strength of the fibers constituting the nonwoven fabric will be reduced. Therefore, there are problems such as a significant reduction in the mechanical properties of the nonwoven fabric, difficulty in performing high-order processing such as pleating and bonding with other components, and deterioration in the mechanical properties of the final product itself.
[0015] Therefore, an object of the present invention is to provide a spunbonded nonwoven fabric which has not only flexibility but also excellent mechanical properties and is easy to perform high-level processing such as pleating and bonding with other members.
[0016] Means for solving problems
[0017] The inventors of the present application have conducted studies and found that making a spunbonded nonwoven fabric more flexible can be achieved by making the fiber diameter smaller and increasing the strength of the fiber itself in terms of excellent mechanical properties.
[0018] In order to make the fiber diameter thinner, it is effective to use a raw material with a high melt flow rate to increase the spinning speed (pulling speed). However, when using a raw material with a high melt flow rate, as mentioned above, the strength of the obtained fiber decreases, so the two have opposite tendencies.
[0019] Therefore, the inventors of the present application conducted further research and conceived the following scheme, namely, in order to further increase the melt flow rate of the raw material, a certain amount of peroxide used as a free radical generator is retained in the spunbonded nonwoven fabric, thereby using it as a crystallization nucleating agent, and the branching degree λ is made within a specific range.
[0020] In addition, based on the above-mentioned findings, the inventors of the present application have conducted intensive studies to solve the above-mentioned problems, and as a result, they have found that, for the fiber polypropylene resin constituting the spunbond nonwoven fabric, by setting the amount of organic peroxide and the degree of branching λ to a specific range and further setting the melt flow rate of the spunbond nonwoven fabric to a specific range, the fiber diameter is made finer and the softness is improved, and by suppressing the defects caused in the nonwoven fabric due to fiber breakage, a high-quality spunbond nonwoven fabric is obtained, and the orientation relaxation of the obtained fibers is suppressed to improve the molecular orientation (Δn), and as a result, the strength of the fibers is improved, thereby obtaining a spunbond nonwoven fabric having excellent mechanical properties and being easy to perform high-order processing such as pleating processing and joining with other components, thereby completing the present invention.
[0021] The present invention aims to solve the above-mentioned problems, and according to the present invention, the following solutions can be provided.
[0022] [1] A spunbond nonwoven fabric comprising fibers formed from a polypropylene resin, wherein the spunbond nonwoven fabric satisfies the following conditions (1) to (3), and the average single fiber diameter of the fibers is 5.0 μm or more and 20.0 μm or less.
[0023] (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 15 minutes, 45 kHz, and a solution temperature of 30° C., and the amount of organic peroxide extracted is 100 ppm or more and 1000 ppm or less;
[0024] (2) The melt flow rate of the polypropylene resin is 20 g / 10 min or more and 400 g / 10 min or less;
[0025] (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
[0026] [2] The spunbonded nonwoven fabric according to [1], wherein the polypropylene resin further satisfies the following conditions (4) and (5).
[0027] (4) 2.50≤Mw / Mn≤3.20;
[0028] (5)1.82≤Mz / Mw≤2.20
[0029] Here, Mw, Mn, and Mz are weight average molecular weight, number average molecular weight, and z average molecular weight respectively determined by gel permeation chromatography.
[0030] [3] The method for producing a spunbonded nonwoven fabric according to [1] or [2], comprising:
[0031] A step of adding an organic peroxide to a raw material resin to decompose the raw material resin to obtain a polypropylene-based resin prepared so as to satisfy the following conditions (1) to (3);
[0032] The step of spinning the polypropylene resin to obtain fibers having an average single fiber diameter of 5.0 μm to 20.0 μm; and
[0033] a step of capturing the fibers,
[0034] (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 15 minutes, 45 kHz, and a solution temperature of 30° C., and the amount of organic peroxide residue extracted is 100 ppm or more and 1000 ppm or less;
[0035] (2) The melt flow rate of the polypropylene resin is 20 g / 10 min or more and 400 g / 10 min or less;
[0036] (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
[0037] [4] The method for producing a spunbonded nonwoven fabric according to [3], wherein the raw material resin is a recycled resin.
[0038] [5] A laminated nonwoven fabric comprising the spunbonded nonwoven fabric described in [1] or [2].
[0039] [6] A sanitary material comprising the spunbonded nonwoven fabric described in [1] or [2] or the laminated nonwoven fabric described in [5].
[0040] [7] Clothing made from the spunbonded nonwoven fabric described in [1] or [2] or the laminated nonwoven fabric described in [5].
[0041] Effects of the Invention
[0042] The spunbonded nonwoven fabric of the present invention has high quality and softness. By allowing a certain amount of organic peroxide to remain in the nonwoven fabric, the oriented crystallization caused by the effect of a crystal nucleating agent is promoted, and by setting the degree of branching λ per molecule to a specific range, the orientation relaxation of the fiber after drawing in the spunbonding process can be suppressed, thereby showing excellent mechanical properties. In addition, the fabric exhibits excellent ease of high-order processing such as pleating processing and joining with other components. DETAILED DESCRIPTION
[0043] The spunbonded nonwoven fabric of the present invention is a spunbonded nonwoven fabric composed of fibers formed from a polypropylene resin, wherein the spunbonded nonwoven fabric satisfies the following conditions (1) to (3), and the average single fiber diameter of the fibers is 5.0 μm or more and 20.0 μm or less.
[0044] (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 15 minutes, 45 kHz, and a solution temperature of 30° C., and the amount of organic peroxide extracted is 100 ppm or more and 1000 ppm or less;
[0045] (2) The melt flow rate is 20 g / 10 minutes to 400 g / 10 minutes;
[0046] (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
[0047] Hereinafter, the spunbonded nonwoven fabric of the present invention will be described in detail, but the present invention is not limited to the following description in any way within the scope of the gist thereof, and various modifications can be made within the scope of the gist of the present invention.
[0048] [Polypropylene resin]
[0049] The spunbonded nonwoven fabric of the present invention is composed of fibers (polypropylene fibers), and the fibers are composed of polypropylene resins. In the present invention, the so-called polypropylene resin refers to a resin in which the molar fraction of propylene units in repeating units is 80 mol% to 100 mol%. By using polypropylene resins, spunbonded nonwoven fabrics with low cost and excellent softness can be made.
[0050] The polypropylene resin used in the present invention includes a homopolymer of propylene or a copolymer of propylene and various α-olefins. When a copolymer of propylene and various α-olefins is used as the polypropylene resin, the copolymerization ratio of various α-olefins is preferably 10 mol% or less, more preferably 5 mol% or less, and further preferably 3 mol% or less in order to further improve the tensile strength of the fiber.
[0051] In the polypropylene resin used in the present invention, other component resins can be mixed within the scope of not damaging the effect of the present invention. As other component resins, polyolefin resins such as polyethylene and poly-4-methyl-1-pentene whose melting points are close to polypropylene can be cited. In addition, low-melting polyester resins and low-melting polyamide resins can also be cited. From the viewpoint of imparting flexibility, it is preferred to use low-crystalline olefin resins. As low-crystalline olefin resins, for example, ethylene-propylene copolymers are preferably used. In this case, in order to fully demonstrate the characteristics of polypropylene resins, the mass ratio of other component resins is preferably 20% by mass or less when the mass ratio of the total of polypropylene resin and other component resins is set to 100% by mass, more preferably 10% by mass or less.
[0052] The polypropylene resin used in the present invention may contain pigments for coloring, antioxidants, lubricants such as polyethylene wax and fatty acid amide compounds, and heat stabilizers, etc., within a range not impairing the effects of the present invention.
[0053] Furthermore, according to a preferred embodiment of the spunbonded nonwoven fabric of the present invention, the polypropylene-based resin further satisfies the following conditions (4) and (5).
[0054] (4) 2.50≤Mw / Mn≤3.20
[0055] (5)1.82≤Mz / Mw≤2.20
[0056] The inventors of the present application have found that the smaller the Mw / Mn and Mz / Mw are, the higher the molecular orientation (Δn) of the obtained fiber is, and the higher the fiber strength is, even at the same spinning speed. From this point of view, Mw / Mn≤2.95 and Mz / Mw≤1.98 are more preferred. On the other hand, by preferably setting 2.50≤Mw / Mn and 1.82≤Mz / Mw, the molecular orientation of the fiber is moderate and the broken yarn is suppressed, thereby forming a high-quality spunbonded nonwoven fabric with few sheet defects.
[0057] The Mw of the polypropylene resin used in the present invention obtained by gel permeation chromatography (hereinafter referred to as GPC) is preferably 120,000 or more and 350,000 or less. Mw is related to MFR. By making Mw less than 350,000, the fluidity of the polypropylene resin becomes higher and the spinnability is improved, so the broken wire defects are reduced. From this viewpoint, the smaller the Mw, the more preferred, more preferably less than 250,000, further preferably less than 210,000, and particularly preferably less than 180,000. On the other hand, by making Mw preferably more than 120,000, more preferably more than 130,000, further preferably more than 150,000, and particularly preferably more than 200,000, the fiber strength can be improved and the sheet defects caused by broken wires can be suppressed.
[0058] In addition, in this invention, Mw, Mn, and Mz are the values measured and calculated by the following method.
[0059] (1) 5 mg test pieces were randomly collected from 5 points of the spunbond nonwoven fabric except for the end portions. The end portions of the spunbond nonwoven fabric refer to 10% of the area at both ends relative to the length in the width direction of the spunbond nonwoven fabric.
[0060] (2) Add 5 mL of 1,2,4-trichlorobenzene (e.g., manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to the test piece obtained in (1). Depending on the properties of the sample, the solution can be easily dissolved by heating at 165°C for 20 minutes. Next, the solution is filtered using a PTFE filter (pore size: 0.45 μm) to prepare a sample solution. Here, the PTFE filter can use, for example, "T010A" manufactured by Advantec Toyo Co., Ltd.
[0061] (3) The sample solution obtained in (2) is measured using GPC under the following conditions. Mw, Mn, and Mz can be determined by analyzing the discharge curve in GPC using, for example, "Empower" manufactured by Wyatt Technology.
[0062] Device: For example, "PL-220" manufactured by Polymer Laboratories, etc.
[0063] Detector: Differential refractive index detector RI
[0064] Chromatographic column: Shodex HT-G (guard column) + Shodex HT-806M × 2 pieces (8.0 mm × 30 cm, such as Showa Denko K.K.)
[0065] Solvent: 1,2,4-trichlorobenzene (with 0.1% BHT added)
[0066] Flow rate: 1.0mL / min
[0067] Column temperature: 145°C
[0068] Injection volume: 0.20mL
[0069] Standard samples: monodisperse polystyrene (for example, products manufactured by Tosoh Corporation), bibenzyl (for example, products manufactured by Tokyo Chemical Industry Co., Ltd.).
[0070] [fiber]
[0071] The spunbond nonwoven fabric of the present invention is composed of fibers formed from the polypropylene resin. Moreover, the average single fiber diameter of the fiber is 5.0 μm or more and 20.0 μm or less. Regarding the range of the average single fiber diameter, by making its upper limit below 20.0 μm, preferably below 16.0 μm, the touch when contacting the surface of the spunbond nonwoven fabric becomes smooth. In addition, due to the thin fiber diameter, the second moment of cross section is reduced, thereby becoming a spunbond nonwoven fabric with excellent softness. On the other hand, regarding the range of the average single fiber diameter, by making its lower limit above 5.0 μm, preferably above 8.0 μm, a spunbond nonwoven fabric with high tensile strength and few defects is obtained.
[0072] It should be noted that the average single fiber diameter (μm) of the fiber in the present invention refers to the value obtained by randomly collecting 10 5mm×5mm test pieces from the area other than the end of the spunbond nonwoven fabric, and for the part other than the embossed bonding part of each test piece, using a digital microscope (for example, "VHX-2000" manufactured by KEYENCE Co., Ltd.) to observe the side of the fiber constituting the spunbond nonwoven fabric, and find the diameter of the fiber, and round off the arithmetic mean (μm) of the diameter of the fiber measured by each test piece to the second decimal place, thereby obtaining. It should be noted that the end of the spunbond nonwoven fabric refers to the area of 10% of the two ends relative to the length in the width direction of the spunbond nonwoven fabric.
[0073] Δn, which is an index of the molecular orientation of the fibers constituting the spunbonded nonwoven fabric of the present invention, is preferably 0.020 or more. By setting Δn to 0.020 or more, not only the orientation of the fibers is improved, the fiber strength and the strength of the sheet are improved, but also the heat resistance is improved, so that thermal bonding such as embossing can be performed at high temperatures, and thermal bonding of the fibers becomes easy, resulting in a spunbonded nonwoven fabric having good mechanical properties and being easy to perform high-order processing such as pleating processing and bonding with other components.
[0074] It should be noted that the Δn of the fibers constituting the spunbonded nonwoven fabric of the present invention refers to a value obtained by randomly collecting 10 test pieces by the same method as the method for measuring the average single fiber diameter, extracting 10 single fibers from the portion other than the embossed bonding portion of the test piece, using a polarizing microscope (for example, "BH2" manufactured by Olympus Corporation), and calculating the delay by a compensation method while immersing the sample in liquid paraffin, and rounding off the arithmetic mean (unitless) of the calculated values to the fourth decimal place to obtain the delay.
[0075] The tensile strength of the fibers constituting the spunbonded nonwoven fabric of the present invention is preferably 2.0 cN / dtex or more. By making the tensile strength of the fibers 2.0 cN / dtex or more, the strength of the sheet is improved, thereby becoming a spunbonded nonwoven fabric having good mechanical properties and being easy to perform high-order processing such as pleating and joining with other components.
[0076] In addition, the tensile strength of the fiber constituting the spunbonded nonwoven fabric of the present invention refers to a value measured and calculated by the following method.
[0077] (1) Ten test pieces are randomly collected by the same method as the above-mentioned measurement of the average single fiber diameter, and 10 single fibers are extracted from the test pieces except for the embossed adhesive portion.
[0078] (2) According to "8.7 Tensile strength and elongation" of JIS L1015:2010 "Testing methods for chemical staple fibers", a single yarn is set with a clamping interval of 20 mm in a tensile testing machine (for example, "UTM-III-100" manufactured by ORIENTEC Co., Ltd.), and a tensile test is carried out at a tensile speed of 20 mm / min to measure the maximum point load (cN).
[0079] (3) Next, the arithmetic mean value (cN / dtex) of the values obtained by dividing the maximum point load by the single yarn fineness (dtex) obtained by the following formula is rounded off to the second decimal place.
[0080] Single fiber fineness (dtex) = π × (average single fiber diameter of fiber (μm) / 2) 2 ×0.91(g / cm 3 )×100000(cm).
[0081] The cross-sectional shape of the fiber constituting the spunbonded nonwoven fabric of the present invention is not particularly limited as long as the effects of the present invention are not impaired. A circular cross-section is not to mention a circular cross-section, and a triangular, elliptical, hexagonal, hollow or other irregular cross-section may be used. A circular cross-section is preferred from the perspective of high productivity and excellent flexibility. That is, when the cross-sectional shape of the polypropylene fiber constituting the spunbonded nonwoven fabric of the present invention is an irregular cross-section, since there is a bending direction in which the second moment of area of the same cross-sectional area is larger than that of a circular cross-section, the spunbonded nonwoven fabric may have high rigidity when made, but a circular cross-section does not have such a bending direction, and therefore has particularly excellent flexibility.
[0082] The fiber constituting the spunbonded nonwoven fabric of the present invention is preferably a composite fiber formed by compounding two or more resins. The composite fiber can be appropriately selected from core-sheath type, island-in-the-sea type, parallel type, eccentric core-sheath type, etc. Among them, the core-sheath type is preferred because of its excellent spinnability and the ability to uniformly bond the fibers to each other by thermal bonding, and a concentric core-sheath type composite form is particularly preferred.
[0083] [Spunbond nonwoven fabric]
[0084] The spunbonded nonwoven fabric of the present invention is a spunbonded nonwoven fabric composed of the fibers formed from the polypropylene resin. As described above, the spunbonded nonwoven fabric has not only softness but also excellent mechanical properties and is easy to be processed by pleating or joining with other parts.
[0085] The spunbonded nonwoven fabric of the present invention satisfies the following conditions (1) to (3).
[0086] (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 15 minutes, 45 kHz, and a solution temperature of 30° C., and the amount of organic peroxide extracted is 100 ppm or more and 1000 ppm or less;
[0087] (2) The melt flow rate is 20 g / 10 minutes to 400 g / 10 minutes;
[0088] (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
[0089] By satisfying all of the conditions (1) to (3), a spunbonded nonwoven fabric not only has flexibility but also has excellent mechanical properties and is easy to perform high-level processing such as pleating and bonding with other components. This will be described in further detail.
[0090] First, regarding the polypropylene resin constituting the spunbonded nonwoven fabric of the present invention, the amount of organic peroxide extracted by ultrasonic treatment of the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent with a volume ratio of 1:1 for 15 minutes and 45kHz is 100 ppm or more and 1000 ppm or less. Regarding the range of the amount of the organic peroxide, by making its lower limit 100 ppm or more, preferably 200 ppm or more, and more preferably 300 ppm or more, it acts as a crystal nucleating agent during the cooling and solidification process during spinning, thereby promoting the oriented crystallization of the molecules. As a result, the molecular orientation (Δn) and fiber strength of the fibers constituting the spunbonded nonwoven fabric can be improved, and a spunbonded nonwoven fabric with excellent mechanical properties can be obtained. On the other hand, regarding the amount of the organic peroxide, by making its upper limit 1000 ppm or less, preferably 800 ppm or less, when used as sanitary materials, protective clothing, etc. for direct contact with the human body, the risk of skin problems such as inflammation caused by organic peroxides can be suppressed to a minimum.
[0091] In addition, in this invention, the said amount of organic peroxide means the value measured and calculated by the following method.
[0092] (1) 25 mg test pieces were randomly collected from 5 points of the spunbonded nonwoven fabric except for the end portions. The end portions of the nonwoven fabric refer to 10% of the region at both ends relative to the length in the width direction of the nonwoven fabric.
[0093] (2) The test piece obtained in (1) is immersed in a chloroform / methanol solvent having a volume ratio of 1:1, and subjected to ultrasonic treatment under the conditions of 15 minutes, 45 kHz, and a solution temperature of 30°C. For the ultrasonic treatment, for example, an ultrasonic cleaner "VS-100III" manufactured by ASONE Co., Ltd. can be used. In addition, the amount of the solvent relative to the mass of the test piece is 0.8 mL of the solvent relative to 1 mg of the test piece, and the extraction is performed while cooling with a refrigerant or the like so that the solution temperature is maintained at 30°C.
[0094] (3) The solution after ultrasonic treatment obtained in (2) is filtered using a filter made of polytetrafluoroethylene (PTFE) (hereinafter, sometimes referred to as "PTFE filter". Pore diameter: 0.45 μm) to obtain a sample solution. Here, regarding the PTFE filter, for example, "T010A" manufactured by Advantec Toyo Co., Ltd. can be used.
[0095] (4) 0.1 g of an organic peroxide is dissolved in 10 mL of a chloroform / methanol solution having a volume ratio of 1:1 to prepare a standard stock solution (10 μg / mL). Then, the standard stock solution is diluted with the chloroform / methanol solution to prepare standard solutions of various concentrations (0.1 μg / mL, 0.2 μg / mL, 0.5 μg / mL, 1.0 μg / mL). At this time, the following substances can be cited as the above-mentioned organic peroxides, and standard solutions of various concentrations are prepared for them respectively. In addition, in the case where an organic peroxide other than the organic peroxide described below is clearly contained or presumed to be contained by other methods (e.g., iodine titration, polarography, etc.), a standard solution of the organic peroxide is also prepared.
[0096] Methyl ethyl ketone peroxide
[0097] Methyl isobutyl ketone peroxide
[0098] Benzoyl peroxide
[0099] ·Di-(3,5,5-trimethylhexanoyl) peroxide
[0100] Dilauroyl peroxide
[0101] ·Didecanoyl peroxide
[0102] ·Di-(2,4-dichlorobenzoyl) peroxide
[0103] tert-Butyl hydroperoxide
[0104] ·Cumene Hydroperoxide
[0105] Diisopropylbenzene hydroperoxide
[0106] 2,5-Dimethylhexane-2,5-dihydroperoxide
[0107] ·Di-tert-butyl peroxide, diisopropylbenzene peroxide
[0108] ·2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexane
[0109] ·2,5-Dimethyl-2,5-bis(tert-butylperoxy)hexyne-3,α,α'-bis(tert-butylperoxy)diisopropylbenzene
[0110] ·1,1-Bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane
[0111] ·2,2-Bis(tert-butylperoxy)butane
[0112] ·tert-Butyl peroxyoctanoate
[0113] ·tert-Butyl peroxypivalate
[0114] ·tert-Butyl peroxyneodecanoate
[0115] ·T-Butyl Perbenzoate
[0116] ·Di(2-ethylhexyl) peroxydicarbonate
[0117] Diisopropyl peroxydicarbonate
[0118] ·Bis(4-tert-butylcyclohexyl)peroxydicarbonate
[0119] ·Di-sec-butyl peroxydicarbonate
[0120] ·tert-Butyl peroxyisopropyl carbonate
[0121] (5) The sample solution was subjected to liquid chromatography-mass spectrometry (LC / MS / MS) analysis under the following conditions.
[0122] High performance liquid chromatography (HPLC): for example, "LC-20A" manufactured by Shimadzu Corporation
[0123] Mass spectrometer (MS) For example, "API4000" manufactured by Sciex, etc.
[0124] Column: ODS series column (such as "SUMIPAX ODS A series" manufactured by Sumika Analytical Center Co., Ltd.)
[0125] Mobile phase: 0.1% formic acid aqueous solution + methanol (gradient extraction conditions)
[0126] Injection volume: 5μL
[0127] Ionization: Electrospray ionization (ESI)
[0128] (6) The organic peroxide was identified by mass spectrometry (MS) of each sample solution, and the amount of the organic peroxide (ppm) was quantified from the peak area using a calibration curve obtained from a standard solution of the organic peroxide.
[0129] (7) The arithmetic mean (ppm) of the values measured for each test piece was rounded off to the first decimal place to determine the amount of organic peroxide (ppm).
[0130] The amount of the organic peroxide in the polypropylene resin constituting the spunbonded nonwoven fabric of the present invention can be controlled by the form and temperature of addition of the organic peroxide to the raw material resin.
[0131] Examples of the organic peroxide used in the present invention include ketone peroxides such as "methyl ethyl ketone peroxide and methyl isobutyl ketone peroxide", diacyl peroxides such as "dibenzoyl peroxide, di-(3,5,5-trimethylhexanoyl) peroxide, dilauroyl peroxide, didecanoyl peroxide, and di-(2,4-dichlorobenzoyl) peroxide", hydroperoxides such as "tert-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylhexane-2,5-dihydroperoxide", and the like, and di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3, α,α'- Dialkyl peroxides such as "bis(tert-butylperoxy)diisopropylbenzene", peroxyketals such as "1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,2-bis(tert-butylperoxy)butane", alkyl peresters such as "tert-butyl peroxyoctanoate, tert-butyl peroxypivalate, tert-butyl peroxyneodecanoate, tert-butyl peroxybenzoate", and peroxycarbonates such as "di(2-ethylhexyl) peroxydicarbonate, diisopropyl peroxydicarbonate, bis(4-tert-butylcyclohexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-butyl peroxyisopropyl carbonate". Among them, dialkyl peroxides are preferred because they are easy to control the melt flow rate and Mw / Mn, Mz / Mw by adding a small amount.
[0132] Secondly, the melt flow rate (hereinafter, sometimes referred to as MFR) of the spunbond nonwoven fabric of the present invention is 20 g / 10 minutes or more and 400 g / 10 minutes or less. Regarding the range of the MFR, by making the lower limit thereof 20 g / 10 minutes or more, preferably 60 g / 10 minutes or more, and more preferably 100 g / 10 minutes or more, a spunbond nonwoven fabric having excellent softness is obtained. On the other hand, by making the upper limit thereof 400 g / 10 minutes or less, preferably 300 g / 10 minutes or less, the mechanical strength of the embossed portion of the spunbond nonwoven fabric is improved, and a spunbond nonwoven fabric having high tensile strength is obtained.
[0133] It should be noted that the MFR of the spunbonded nonwoven fabric in the present invention is obtained by the following method: According to "Chapter 8 A: Mass Measurement Method" of JIS K7210-1:2014 "Plastics-Methods for determining melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastics-Part 1: Standard test methods", 5 test pieces of 20 g each are randomly collected from the area other than the end of the spunbonded nonwoven fabric, and for each test piece, the arithmetic mean of the value (g / 10 minutes) measured under the conditions of a load of 2160 g and a temperature of 230°C is rounded to the first decimal place to obtain the MFR (g / 10 minutes). It should be noted that the end of the nonwoven fabric refers to the 10% area of the two ends relative to the length in the width direction of the nonwoven fabric. In addition, in the measurement, for example, a melt index tester "F-F01" manufactured by Toyo Seiki Seisaku-sho, Ltd. can be used.
[0134] In addition, the MFR of the spunbonded nonwoven fabric can be controlled by the weight average molecular weight of the polypropylene resin. The higher the weight average molecular weight of the polypropylene resin, the smaller the melt flow rate becomes. The weight average molecular weight can be controlled by the weight average molecular weight of the raw material resin and the amount of organic peroxide added.
[0135] The spunbonded nonwoven fabric of the present invention has a branching degree λ per molecule of the polypropylene resin (hereinafter, sometimes referred to as the branching degree λ per molecule) calculated using the trifunctional random branching theory using the molecular weight and the gyration radius obtained by gel permeation chromatography / multi-angle light scattering measurement (hereinafter, sometimes referred to as GPC-MALS) of 1.0×10 -7 Above 1.0×10 -3 The range of the degree of branching λ per molecule is as follows: -7 More than, preferably 1.0×10 -6 More preferably, 5.0×10 -6 The above range can be made into a spunbonded nonwoven fabric with a higher fiber strength and excellent mechanical properties by making the molecular structure of the polypropylene resin more branched. -3 Less than, preferably 1.0×10 -4 Less than, more preferably 5.0×10 -5 Thus, it is possible to suppress fiber breakage during spinning due to an excessive branched structure, thereby achieving a high-quality spunbonded nonwoven fabric with fewer defects.
[0136] In addition, in this invention, the said branching degree λ per 1 molecule means the value measured and calculated by the following method.
[0137] (1) 5 mg test pieces were randomly collected from 5 points of the spunbond nonwoven fabric except for the end portions. The end portions of the nonwoven fabric refer to 10% of the area at both ends relative to the length in the width direction of the nonwoven fabric.
[0138] (2) Add 5 mL of 1,2,4-trichlorobenzene (e.g., manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to the test piece obtained in (1). If the sample is difficult to dissolve, the solution may be heated at 165°C for 20 minutes to dissolve it. Next, filter the solution using a PTFE filter (pore size: 0.45 μm, e.g., "T010A" manufactured by Advantec Toyo Co., Ltd.) to prepare a sample solution.
[0139] (3) The sample solution obtained in (2) was measured using GPC-MALS under the following conditions.
[0140] Gel permeation chromatography (GPC): for example, "HLC-8321GPC / HT" manufactured by Tosoh Corporation
[0141] Differential refractive index detector: for example, "HL-8321GPC / HT" manufactured by Tosoh Corporation
[0142] Multi-angle light scattering detector (MALS): for example, "DAWNNEON" manufactured by Wyatt Technology, etc.
[0143] Chromatographic column: For example, "Shodex HT-806M" manufactured by Showa Denko K.K.
[0144] Solvent: 1,2,4-trichlorobenzene (added with 0.1% BHT, for example, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0145] Column temperature / detector temperature: 145℃ / 145℃
[0146] Sample solution injection volume: 0.300mL
[0147] Data processing unit: GPC: for example, "Empower" manufactured by Wyatt Technology, MALS: for example, "ASTRA 8.0.1.21" manufactured by Wyatt Technology, etc.
[0148] (4) For each sample solution, the molecular weight and the rotation radius at each dissolution time are calculated based on the obtained GPC-MALS curve using the data processing software. Here, regarding the relationship between the molecular weight and the rotation radius, it is known that compared with a linear polypropylene resin without a branched structure (for example, "'NOVATEC' (registered trademark) PP FY6" manufactured by Japan Polypropylene Co., Ltd.), a polypropylene resin with a branched structure has a smaller rotation radius at the same molecular weight. In the 3-functional group random branching theory, the rotation radius S is related to the number of branching points λ at each molecular weight. M The following equation holds.
[0149] [Mathematical formula 1]
[0150]
[0151] (where g = (radius of rotation S of the sample) 2 / (Radius of rotation S of linear polypropylene) 2 . )
[0152] (5) Using the above formula, calculate the branching point number λ of each sample M Next, the branch point number λ M The value obtained by dividing by the corresponding absolute molecular weight (unitless) was rounded off to the second decimal place to calculate the number of branching points per molecule (unitless).
[0153] (6) Among the branching points per molecule calculated in (5), the maximum value in the range of absolute molecular weight of 100,000 or more is taken as the branching degree λ per molecule. -8 The following cases were below the detection limit and were therefore regarded as 0.
[0154] The degree of branching λ per molecule can be controlled by the degree of branching λ per molecule of the raw material resin used. For example, the greater the degree of branching λ per molecule of the raw material resin, the greater the degree of branching λ of the polypropylene resin.
[0155] In addition, the weight per unit area of the spunbonded nonwoven fabric of the present invention is preferably 3 g / m 2 Above 50g / m 2 The range of the weight per unit area is preferably 3 g / m2 by setting the lower limit thereof. 2 More preferably 5g / m 2 The above-mentioned spunbonded nonwoven fabric has sufficient strength, less breakage in the subsequent process, and excellent processability. In addition, regarding the range of the weight per unit area, the upper limit is preferably 50 g / m 2 Below, 30g / m 2Hereinafter, the softness of the spunbonded nonwoven fabric can be appropriately exhibited.
[0156] The weight per unit area of the spunbonded nonwoven fabric in the present invention is obtained as follows: According to "6.2 Mass per unit area (ISO method)" of JIS L1913:2010 "General nonwoven fabric test methods", three test pieces of 20 cm × 25 cm are randomly collected from the portion of the spunbonded nonwoven fabric excluding the end portions per 1 m width, and the mass (g) of each test piece under the standard state is weighed, and the arithmetic mean (g) is calculated and converted into the mass per 1 m 2 Mass (g / m 2 ), rounding off the first decimal place. It should be noted that the end portion of the nonwoven fabric refers to a 10% region at both ends relative to the length in the width direction of the nonwoven fabric.
[0157] The spunbonded nonwoven fabric of the present invention preferably has a tensile strength per unit area weight of 0.30 (N / 25 mm) / (g / m 2 ) or more 5.00(N / 25mm) / (g / m 2 ) or less. The range of tensile strength per unit area weight is preferably 0.3 (N / 25mm) / (g / m 2 ) or more, more preferably 0.50 (N / 25mm) / (g / m 2 ) or more, more preferably 0.70 (N / 25mm) / (g / m 2 ) or more, so as to withstand the process of manufacturing diapers, etc., and the use as a product; about the said range, by making its upper limit preferably 5.00 (N / 25mm) / (g / m 2 ) or less, so it has both softness and flexibility.
[0158] In the present invention, the tensile strength per unit area weight of the spunbonded nonwoven fabric refers to a value measured by the following procedure in accordance with "6.3 Tensile strength and elongation (ISO method)" of JIS L1913:2010 "General nonwoven fabric test methods".
[0159] (1) Three test pieces of 25 mm × 30 mm were randomly collected from the region of the spunbonded nonwoven fabric excluding the end portions in the longitudinal direction and the width direction of the nonwoven fabric. It should be noted that the end portions of the nonwoven fabric refer to the region of 10% of both ends relative to the length in the width direction of the nonwoven fabric.
[0160] (2) The test piece is set in a tensile testing machine with a clamping interval of 20 mm.
[0161] (3) A tensile test was performed at a tensile speed of 20 mm / min to measure the maximum point load (N / 25 mm). The arithmetic mean value (N / 25 mm) of all the maximum point loads measured in the longitudinal direction and the width direction of each test piece was calculated.
[0162] (4) According to the weight per unit area (g / m 2 ), the arithmetic mean of the maximum point load (N / 25mm), and the tensile strength per unit area weight are calculated according to the following formula, rounding off to the third decimal place.
[0163] Tensile strength per unit area weight (N / 25mm) / (g / m 2 )) = Arithmetic mean of maximum point load (N / 25mm) / weight per unit area (g / m 2 ).
[0164] The stiffness of the spunbonded nonwoven fabric of the present invention is preferably 0.5 mN·cm or more and 3.0 mN·cm or less. Stiffness is an index of softness, and by being 3.0 mN·cm or less, high softness can be obtained. The lower the stiffness, the better the softness, so the stiffness is more preferably 2.0 mN·cm or less. On the other hand, if the stiffness is too low, it is easy to be caught by the roller and difficult to perform high-order processing such as pleating processing and joining with other components, so the stiffness is preferably 0.5 mN·cm or more, and more preferably 1.0 mN·cm or more.
[0165] The stiffness of the spunbonded nonwoven fabric of the present invention refers to a value measured by the following procedure in accordance with "6.7.3 41.5° cantilever method" of JIS L1913:2010 "General nonwoven fabric test methods".
[0166] (1) Three test pieces of 25 mm × 250 mm were randomly collected from the region of the spunbonded nonwoven fabric excluding the end portions in the longitudinal direction and the width direction of the nonwoven fabric. It should be noted that the end portions of the nonwoven fabric refer to the region of 10% of both ends relative to the length in the width direction of the nonwoven fabric.
[0167] (2) Place the test piece on a 41.5° cantilever testing machine and slowly push the steel ruler and the test piece along the inclined surface at a constant speed.
[0168] (3) Move the steel ruler until the test piece contacts the inclined surface, and read the protruding length of the test piece from the steel ruler to 1 mm. For each test piece, perform four measurements on the front, back, and both ends, and take half of their arithmetic mean as the bending length (cm).
[0169] (4) Furthermore, the arithmetic mean (cm) of the bending lengths of all the test pieces in each of the longitudinal direction and the width direction is calculated, and the second decimal place is rounded off to obtain the total average bending length (cm).
[0170] (5) According to the weight per unit area (g / m 2 ), the total average bending length (cm), and the stiffness (mN·cm) were calculated by the following formula, rounding off to the second decimal place.
[0171] Stiffness (mN·cm) = Weight per unit area (g / m 2 )×[total average bending length (cm)] 3 ×10 -3 .
[0172] [Method for producing spunbonded nonwoven fabric]
[0173] The method for producing a spunbonded nonwoven fabric of the present invention comprises: a step of adding an organic peroxide to a raw material resin to decompose the raw material resin to obtain a polypropylene resin prepared in a manner satisfying the following conditions (1) to (3); a step of spinning the polypropylene resin to obtain fibers having an average single fiber diameter of 5.0 μm to 20.0 μm; and a step of capturing the fibers.
[0174] (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 45 kHz for 15 minutes, and the amount of organic peroxide residue extracted is 100 ppm or more and 1000 ppm or less;
[0175] (2) The melt flow rate of the polypropylene resin is not less than 20 g / 10 minutes and not more than 400 g / 10 minutes;
[0176] (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
[0177] In this regard, a specific example will be described.
[0178] (a) Step of obtaining polypropylene resin
[0179] In the method for manufacturing a spunbonded nonwoven fabric of the present invention, first, an organic peroxide is added to a raw material resin to decompose the raw material resin. The raw material resin used at this time refers to a resin in which the molar fraction of propylene units in the repeating units is 80 mol% to 100 mol%. Therefore, as specific examples of the raw material resin, homopolymers of propylene or copolymers of propylene and various α-olefins can be cited. When a copolymer of propylene and various α-olefins is used as a raw material resin, in order to improve the tensile strength of the spunbonded nonwoven fabric, the copolymerization ratio of various α-olefins is preferably 10 mol% or less, more preferably 5 mol% or less, and further preferably 3 mol% or less.
[0180] Alternatively, it is also one of preferred embodiments that the raw resin is a recycled resin. In the present invention, recycled resin refers to a resin formed from process scraps generated when manufacturing products and finished products, with more than 10% by mass of the resin. As an example of process scraps generated when manufacturing products, the end material of the film, fabric, and scraps of non-woven fabrics can be cited. In this technology, the raw resin is decomposed in a manner that meets specific conditions. As the raw resin, a resin with a wide range of MFR can be applied, so it is suitable to use recycled resin. Thus, the usage of original petrochemical raw materials can be reduced, and the environmental load during the manufacture of spunbond nonwoven fabrics can be reduced.
[0181] The raw material resin used in the present invention may contain pigments for coloring, antioxidants, lubricants such as polyethylene wax and fatty acid amide compounds, and heat stabilizers, etc., within a range not impairing the effects of the present invention.
[0182] Examples of the organic peroxide used in the method for producing the spunbonded nonwoven fabric of the present invention include organic peroxides described in [Spunbonded nonwoven fabric].
[0183] As described above, the polypropylene resin obtained by adding the organic peroxide to the raw material resin and decomposing the raw material resin so as to satisfy the above conditions (1) to (3) can also be directly supplied to the spinning described later without being particularly dried, etc. It should be noted that the organic peroxide can be kneaded and pelletized in an extruder before being supplied to the spinning described later to obtain the polypropylene resin, or the organic peroxide and the polypropylene resin can be kneaded in an extruder used for spinning to obtain the polypropylene resin at the same time of melt spinning.
[0184] Here, regarding the method for adjusting the MFR of the polypropylene resin, the MFR of the obtained polypropylene resin can be increased by increasing the amount of organic peroxide added. In addition, if the amount of addition is constant, the higher the MFR of the raw material resin, the higher the MFR of the obtained polypropylene resin. In addition, regarding the measurement of the MFR of the raw material resin, in the same manner as the method for measuring the MFR of the spunbonded nonwoven fabric, according to "Chapter 8 A: Mass Measurement Method" of JIS K 7210-1:2014 "Plastics-Method for Determination of Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) of Thermoplastics-Part 1: Standard Test Methods", 5 samples of 20 g of the raw material resin are prepared, and for each sample, the arithmetic mean of the values (g / 10 minutes) measured under the conditions of a load of 2160 g and a temperature of 230°C is rounded to the first decimal place to obtain the MFR (g / 10 minutes). In addition, for the measurement, for example, a melt indexer "F-F01" manufactured by Toyo Seiki Seisaku-sho, Ltd. or the like can be used.
[0185] In addition, from the viewpoint of obtaining a spunbonded nonwoven fabric having high tensile strength, the branching degree λ per molecule of the raw material resin, which is calculated using the molecular weight and the gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device and the trifunctional random branching theory, is preferably as large as possible, and is preferably 1.0×10 -7 On the other hand, by setting the branching degree λ per molecule of the raw material resin to preferably 1.0×10 -3 As a result, it is possible to suppress fiber breakage during spinning due to an increase in the elongational viscosity of the obtained polypropylene resin.
[0186] The degree of branching λ per molecule of the raw material resin can be measured and calculated by the same method as the degree of branching λ per molecule of the polypropylene resin.
[0187] In addition, in the raw material resin used in the present invention, other component resins can be mixed within the scope of not damaging the effect of the present invention. As other component resins, in addition to polyolefin resins such as polyethylene and poly-4-methyl-1-pentene whose melting points are close to polypropylene, low melting point polyester resins and low melting point polyamide resins can also be cited. From the viewpoint of imparting flexibility, low-crystalline olefin resins can be preferably used. As low-crystalline olefin resins, for example, ethylene-propylene copolymers are preferably used. In this case, in order not to damage the characteristics of polypropylene resins, particularly the heat resistance of spunbonded nonwoven fabrics, the mass ratio of other component resins is preferably 20% by mass or less, more preferably 10% by mass or less.
[0188] Furthermore, the amount of the organic peroxide remaining in the polypropylene-based resin can be controlled by the temperature at which the organic peroxide is added to the raw material resin and the form of the peroxide.
[0189] First, when adding an organic peroxide to the raw material resin in the extruder, the amount of residual organic peroxide decreases by increasing the extrusion temperature. On the other hand, if the extrusion temperature is lowered, the amount of residual organic peroxide increases. In view of the melting point of the polypropylene resin as the raw material resin, the extrusion temperature is preferably 180°C or higher, more preferably 200°C or higher. On the other hand, in order to prevent the risk of yellowing and ignition caused by oxidative decomposition of the polypropylene resin, the extrusion temperature is preferably 280°C or lower, more preferably 260°C or lower.
[0190] By adding the organic peroxide in the form of masterbatch of the polypropylene resin, self-decomposition in the extruder is suppressed under the conditions of constant addition amount and extrusion temperature, so that a large amount of the organic peroxide can remain in the polypropylene resin.
[0191] (b) Process of obtaining fibers
[0192] In this step, the polypropylene resin is spun to obtain fibers having an average single fiber diameter of 5.0 μm to 20.0 μm.
[0193] In the spinning, a melt spinning method using an extruder such as a single screw or twin screw extruder can be applied. In addition, the polypropylene resin extruded from the extruder is metered through a metering device such as a gear pump via a pipe, passes through a filter to remove foreign matter, and then is guided to a spinning spinneret. At this time, in order to improve fluidity, the temperature (spinning temperature) from the resin pipe to the spinning spinneret is preferably 180°C or more and 280°C or less.
[0194] The spinning spinneret used for ejection preferably has a spinneret hole diameter D of 0.1 mm or more and 1.0 mm or less. In addition, the L / D defined by the quotient of the land length L of the spinneret (the length of the straight tube portion with the same hole diameter as the spinneret hole) divided by the hole diameter D is preferably 1 or more and 10 or less.
[0195] The yarn ejected from the spinneret hole can be cooled and solidified by blowing air. From the viewpoint of cooling efficiency, the temperature of the cooling air in this case can be determined by the balance with the cooling air speed, and from the viewpoint of uniformity of fineness, it is preferably above 0°C and below 20°C. By making the temperature of the cooling air preferably above 0°C, more preferably above 2°C, condensation and freezing of the air piping and the cooling air discharge part can be prevented, and the cooling air can be supplied stably. In addition, by making the temperature of the cooling air preferably below 20°C, more preferably below 16°C, and further preferably below 12°C, the cooling effect of the fiber is improved, the uniformity is increased, and a spunbonded nonwoven fabric with fewer broken yarn defects is obtained.
[0196] The cooling gas cools the yarn by flowing in a direction substantially perpendicular to the yarn (in the case of the fiber running up and down, it means a direction parallel to the ground). At this time, the speed of the cooling air is preferably 10 m / min or more and 100 m / min or less. By setting the cooling air speed preferably to 10 m / min or more, the cooling effect is improved, the uniformity is increased, and a spunbonded nonwoven fabric with fewer broken yarn defects is obtained. In addition, by setting the cooling air speed preferably to 100 m / min or less, the yarn swing caused by the cooling air can be suppressed, so that the broken yarn during spinning is reduced.
[0197] The distance from the spinneret of the spinning spinneret to the position where cooling starts is preferably 20 mm or more and 800 mm or less. With respect to the range of the distance, by making its lower limit preferably 20 mm or more, the spinneret surface temperature will not be excessively reduced, the ejection is stable, and thus the broken wires during spinning are reduced. In addition, with respect to the range of the distance, by making its upper limit preferably 800 mm or less, the cooling effect is improved, the uniformity is increased, and a spunbonded nonwoven fabric with fewer broken wire defects is obtained.
[0198] Regarding the yarn ejected from the spinneret, regardless of whether cooling air is blown or not, air pulling (pulling by accelerated air flow) is performed at a position preferably within 400 mm and 700 mm from the spinneret. Regarding the accelerated air flow, the air flow rate can be accelerated by sealing the area where the cooling air is blown and gradually reducing the cross-sectional area of the sealed area toward the downstream of the spinning line, but in order to obtain a higher air flow rate, the use of an ejector is a preferred embodiment. The yarn is accelerated by the air flow rate, and the spinning speed, which is the traveling speed of the fiber, also reaches a speed close to the air flow rate. It should be noted that in the present invention, the gas used for air pulling is not limited to ordinary air, but can also be nitrogen, and if the humidity is below 100% RH, it can also be water vapor.
[0199] In order to reduce the average single fiber diameter, the spinning speed is preferably 3 km / minute or more, more preferably 4 km / minute. In addition, similarly, the air flow rate is also preferably 3 km / minute or more. In addition, the upper limit of the spinning speed is about 12 km / minute.
[0200] The spinning speed is a value calculated by the following formula.
[0201] Spinning speed (km / min) = Q·1000 / ((W / 2) 2 ×π×ρ)
[0202] (Where Q represents the discharge volume per hole (g / min), W represents the average single fiber diameter (μm), and ρ represents the density (g / cm 3 ). Regarding the polypropylene resin used in the present invention, the value of density is 0.91. In addition, the value of the average single fiber diameter is the value measured and calculated by the method described in the above [Fiber].
[0203] Thus, fibers having an average single fiber diameter of 5.0 μm or more and 20.0 μm or less are formed.
[0204] (c) Fiber Capture Step
[0205] The air-drawn yarn (fiber) can be collected by passing through a fiber-spreading section where the surrounding air velocity is reduced to spread the yarn, and then landing on a net conveyor that sucks air from the back to be collected in the form of a fiber net.
[0206] (d) Post-processing
[0207] Then, the captured fiber web can be directly used as a spunbond nonwoven fabric, but it is more preferable to obtain a spunbond nonwoven fabric by conveying the fiber web at a speed of 10 m / min to 1000 m / min and subjecting the fiber web to a thermal bonding process. As a method of integrating the fibers constituting the above-mentioned fiber web by thermal bonding, there can be cited a method of thermal bonding using the following various rollers: a pair of upper and lower heat embossing rollers, each of which has an engraving (concave and convex portion) on the roller surface; a combination of heat embossing rollers including a roller with a flat (smooth) surface and a roller with an engraving (concave and convex portion) on the roller surface; and a combination of heat calendering rollers including a pair of upper and lower flat (smooth) rollers; and the like.
[0208] The embossed bonding area ratio during thermal bonding is preferably 5% or more and 30% or less. By setting the bonding area preferably to 5% or more, the spunbonded nonwoven fabric has a high tensile strength that can be actually used as a spunbonded nonwoven fabric, and is easy to perform high-order processing such as pleating and joining with other components. On the other hand, by setting the bonding area preferably to 30% or less, sufficient softness can be obtained when the spunbonded nonwoven fabric is used as a sanitary material, in particular.
[0209] The so-called bonding area in the present invention refers to the proportion of the portion where the convex portion of the upper roller overlaps the convex portion of the lower roller and contacts the fiber web in the entire nonwoven fabric when thermal bonding is performed by a pair of rollers with convex and concave portions. In addition, when thermal bonding is performed by a roller with convex and concave portions and a flat roller, it refers to the proportion of the portion where the convex portion of the roller with convex and concave portions contacts the fiber web in the entire nonwoven fabric.
[0210] As the shape of the engraving provided to the heat embossing roll, a circle, an ellipse, a square, a rectangle, a parallelogram, a rhombus, a regular hexagon, a regular octagon, or the like can be used.
[0211] In the manufacture of the spunbonded nonwoven fabric of the present invention, the important point in terms of technology is that the average single fiber diameter can be reduced by high-speed spinning and the stable production thereof can be performed. Although the mechanism is not yet clear, the spunbonded nonwoven fabric of the present invention uses a polypropylene resin with a high MFR as a raw material, so the deformation followability of the polypropylene resin in the thinning behavior in the spinning process is improved, thereby significantly reducing the broken fiber defects.
[0212] On the other hand, if only the above points are considered, the obtained spunbonded nonwoven fabric has problems such as low tensile strength due to high MFR, difficulty in high-order processing such as pleating and bonding with other parts. Therefore, another important point in the process of manufacturing the spunbonded nonwoven fabric of the present invention is that Δn, which is an index of molecular orientation of the fiber, can be increased by the effect of the crystallization nucleating agent brought by the organic peroxide and the effect of suppressing orientation relaxation by the branched structure, and the strength of the fiber can be increased.
[0213] The spunbonded nonwoven fabric thus obtained has not only excellent softness but also sufficient tensile strength for use in spunbonded nonwoven fabrics and is easily subjected to advanced processing such as pleating and joining with other members.
[0214] [Laminated nonwoven fabric]
[0215] The laminated nonwoven fabric of the present invention includes the spunbonded nonwoven fabric. Although the spunbonded nonwoven fabric of the present invention has excellent tensile strength when it is alone, it exhibits more excellent mechanical properties by laminating with a heat-fusible nonwoven fabric. The so-called heat-fusible nonwoven fabric, for example, can include a meltblown nonwoven fabric with a low softening temperature and excellent heat-fusible properties, and a spunbonded nonwoven fabric formed from a low-melting-point polypropylene resin polymerized by a metallocene catalyst. Moreover, as a laminated structure of the laminated nonwoven fabric, the spunbonded nonwoven fabric is set to S and the meltblown nonwoven fabric is set to M, for example, S / M, S / S, S / M / M, M / S / M, S / S / M, S / M / S, S / M / M / S, S / M / M / M / S, S / M / M / M / S, etc. can be cited. A preferred method for producing the laminated nonwoven fabric is to laminate the nonwoven fabric layers ejected from a plurality of spinning spinnerets on a conveyor and bond the obtained laminated web portions together using an embossing roll or the like.
[0216] [Sanitary materials, clothing]
[0217] The sanitary material and clothing of the present invention are formed by having a spunbonded nonwoven fabric or the laminated nonwoven fabric in at least a portion thereof. The spunbonded nonwoven fabric and the laminated nonwoven fabric have excellent softness and skin touch, uniform texture, and sufficient tensile strength for practical use, so that sanitary materials and clothing with excellent comfort when worn can be obtained.
[0218] It should be noted that the sanitary materials and clothing referred to herein are disposable items mainly used for health-related purposes such as medical treatment and nursing care.
[0219] The sanitary material of the present invention includes diapers, sanitary napkins, gauze, bandages, masks, gloves, bandages, etc., and its components include, for example, top sheets, back sheets, side pleats, etc. in diapers. Among them, the back sheet of diapers requiring high tensile strength and softness is suitable.
[0220] The clothing of the present invention includes protective clothing used in medical fields, examination clothing, surgical gowns, work clothes or dustproof clothing used in clean rooms, and the like. The components thereof include, for example, an inner layer component that comes into direct contact with the skin, an intermediate layer component that requires a barrier function, and an outer layer component. Among them, the inner layer of the protective clothing that requires high tensile strength and flexibility is suitable.
[0221] Example
[0222] Hereinafter, the spunbonded nonwoven fabric of the present invention will be described in more detail with reference to examples.
[0223] [Measurement and evaluation methods]
[0224] The various characteristic values in the examples were determined by the following methods. In addition, unless otherwise specified, the measurement method was performed by the above-mentioned method.
[0225] A. MFR of raw resin and spunbond nonwoven fabric:
[0226] The MFR of the spunbonded nonwoven fabric was measured according to the above method using a melt indexer "F-F01" manufactured by Toyo Seiki Seisaku-sho, Ltd.
[0227] B. Quantification of organic peroxides in raw resin and spunbonded nonwoven fabrics:
[0228] The amount of organic peroxide in the spunbond nonwoven fabric was measured and calculated using "LC-20A" manufactured by Shimadzu Corporation as a high performance liquid chromatography (HPLC), "API4000" manufactured by Sciex as a mass spectrometer (MS), and "SUMIPAX ODS A Series" manufactured by Sumika Analytical Center Co., Ltd. as a chromatographic column.
[0229] The lower limit of detection in the above measurement is 5 ppm, so when no organic peroxide was detected, it is recorded as <5 [ppm] in the table.
[0230] C. Degree of branching of raw resin and spunbonded nonwoven fabric:
[0231] The degree of branching λ of the spunbonded nonwoven fabric was measured using "HLC-8321GPC / HT" manufactured by Tosoh Corporation as a gel permeation chromatograph (GPC), "HL-8321GPC / HT" manufactured by Tosoh Corporation as a differential refractive index detector, "DAWNNEON" manufactured by Wyatt Technology as a multi-angle light scattering detector (MALS), and "Shodex HT-806M" manufactured by Showa Denko K.K. as a chromatographic column. The data analysis of the discharge curve was performed using "Empower" manufactured by Wyatt Technology and "ASTRA 8.0.1.21" manufactured by Wyatt Technology, and "'NOVATEC' (registered trademark) PP FY6" manufactured by Japan Polypropylene Co., Ltd. was used as a linear polypropylene resin without a branched structure, and was measured and calculated by the above method.
[0232] D. Mn, Mw, Mz of raw resin and spunbonded nonwoven fabric:
[0233] Regarding Mn, Mw, and Mz of polypropylene resin, "T010A" manufactured by Advantec Toyo Co., Ltd. was used as a PTFE filter, "PL-220" manufactured by Polymer Laboratories was used as an apparatus, Shodex HT-G (guard column) + Shodex HT-806M×2 roots (8.0 mm×30 cm, manufactured by Showa Denko K.K.) were used as chromatographic columns, monodisperse polystyrene manufactured by Tosoh Corporation and bibenzyl manufactured by Tokyo Chemical Industry Co., Ltd. were used as standard samples, and the above-mentioned method was used for measurement. The data analysis of the discharge curve was performed using "Empower" manufactured by Wyatt Technology.
[0234] E. Average single fiber diameter and spinning speed:
[0235] The average single fiber diameter of the fibers was measured using "VHX-2000" manufactured by KEYENCE CORPORATION. The spinning speed (km / min) was determined from the average single fiber diameter obtained using the above formula.
[0236] F. Molecular orientation of fiber Δn:
[0237] The molecular orientation Δn of the fiber was measured by the above-mentioned method using "BH2" manufactured by Olympus Corporation as a polarizing microscope.
[0238] G. Tensile strength of fiber:
[0239] The tensile strength (cN / dtex) of the fiber was measured by the above-mentioned method using "UTM-III-100" manufactured by ORIENTEC CORPORATION as a tensile testing machine.
[0240] H. Weight per unit area of spunbond nonwoven fabric:
[0241] The basis weight of the spunbonded nonwoven fabric was measured and calculated by the above-mentioned method.
[0242] I. Tensile strength per unit area weight of spunbond nonwoven fabric:
[0243] The tensile strength per unit area weight of the spunbonded nonwoven fabric was measured and calculated by the above-mentioned method using "UTM-III-100" manufactured by ORIENTEC CORPORATION as a tensile testing machine.
[0244] J. Stiffness of spunbond nonwoven fabric:
[0245] The stiffness of the spunbonded nonwoven fabric was measured by the above method.
[0246] K. Number of defects of spunbond nonwoven fabrics:
[0247] Use a magnifying glass to visually observe a 10 cm square area outside the end of the spunbonded nonwoven fabric. The portion where the fiber diameter is more than 2 times larger than the average fiber diameter due to broken fibers and the portion where the cut edge of the fiber is rounded and appears to be more than 2 times larger than the average fiber diameter are treated as defects and their number is counted. Repeat this observation 5 times in the length (MD) direction of the nonwoven fabric, and the total number is taken as the number of defects (pieces) of the spunbonded nonwoven fabric. It should be noted that the end of the nonwoven fabric refers to the 10% area at both ends relative to the length in the width direction of the nonwoven fabric.
[0248] L. High-order processing of spunbond nonwoven fabrics:
[0249] In order to understand the ease of high-order processing such as pleating and joining with other parts, prepare a sheet test piece (width: 100mm, length: 300m) of the spunbond nonwoven fabric except the end, and make it travel between a pair of silicone rubber (hardness 12°) rollers (rubber part outer diameter: 15cm, surface roughness Ra: 6.3μm) with a line pressure set to 300N / cm at 20m / min for 10 minutes. At this time, observe whether the fibers, etc. are attached to the rollers and the state of the spunbond nonwoven fabric, and score them using the following criteria as processability (points). Those with 4 points or more are judged as spunbond nonwoven fabrics with excellent processability. It should be noted that the end of the nonwoven fabric refers to the 10% area at both ends relative to the length in the width direction of the nonwoven fabric.
[0250] 5 points: No fibers were attached to the roller, and no fuzz or tears of the nonwoven fabric were observed.
[0251] 4 points: Fibers were attached to the roller, but no fuzz or tearing of the nonwoven fabric was observed.
[0252] 3 points: Fibers are attached to the roller and there is lint from the nonwoven fabric, but no breakage is observed.
[0253] 2 points: Fibers are attached to the roller, and there is fluff from the nonwoven fabric and the roller is torn.
[0254] 1 point: The nonwoven fabric was wound around the roll due to sheet breakage.
[0255] M. Effects of spunbond nonwoven fabrics on skin:
[0256] A 10 cm square test piece collected from the area other than the end of the spunbond nonwoven fabric was cultured in a culture medium at 37°C for 24 hours together with the "LabCyte EPI-MODEL24well 6-day culture product" (assuming a human epidermis model of sensitive skin) manufactured by Japan Tissue Engineering Co., Ltd. After culture, based on ISO 10993-5:2009 "Biological evaluation of medical equipment" Annex C, 3-(4,5-dimethyl-2-thiazole)-2,5-diphenyltetrazolium bromide (MTT) reagent was added for pigment detection, and the absorbance of OD570 was measured, thereby calculating the cell survival rate (%), and evaluating it using the following criteria (0, △, ×).
[0257] ○: Cell survival rate is more than 99%
[0258] △: Cell survival rate is 95% or more and less than 99%
[0259] ×: Cell viability is less than 95%
[0260] In addition, the edge part of a nonwoven fabric refers to the area|region which is 10% of both ends with respect to the length of the width direction of a nonwoven fabric.
[0261] [Raw material resin, polypropylene masterbatch, organic peroxide]
[0262] The raw material resins, polypropylene master batches, and organic peroxides used in Examples and Comparative Examples are shown below.
[0263] (Raw material resin A)
[0264] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, having an MFR of 6 g / 10 min, an Mw of 458,000, an Mw / Mn of 5.31, an Mz / Mw of 2.79, and a branching degree λ of 1.0×10 -6 .
[0265] (Raw material resin B)
[0266] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, has an MFR of 0.3 g / 10 min, an Mw of 1319362, an Mw / Mn of 6.31, an Mz / Mw of 3.06, and a branching degree λ of 1.0×10 -6 .
[0267] (Raw material resin C)
[0268] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, having an MFR of 0.05 g / 10 min, an Mw of 2483427, an Mw / Mn of 7.55, an Mz / Mw of 4.79, and a branching degree λ of 1.0×10 -6 .
[0269] (Raw material resin D)
[0270] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, having an MFR of 10 g / 10 min, an Mw of 382638, an Mw / Mn of 4.90, an Mz / Mw of 2.54, and a branching degree λ of 1.0×10 -6 .
[0271] (Raw material resin E)
[0272] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, having an MFR of 15 g / 10 min, an Mw of 331610, an Mw / Mn of 4.55, an Mz / Mw of 2.45, and a branching degree λ of 1.0×10 -6 .
[0273] (Raw material resin F)
[0274] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, having an MFR of 0.01 g / 10 min, an Mw of 4383165, an Mw / Mn of 7.98, an Mz / Mw of 5.11, and a branching degree λ of 1.0×10 -6 .
[0275] (Raw material resin G)
[0276] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, has an MFR of 0.3 g / 10 min, an Mw of 1319362, an Mw / Mn of 6.31, an Mz / Mw of 3.06, and a branching degree λ of 1.0×10 -5 .
[0277] (Raw material resin H)
[0278] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, has an MFR of 0.3 g / 10 min, an Mw of 1319362, an Mw / Mn of 6.31, an Mz / Mw of 3.06, and a branching degree λ of 1.0×10 -7 .
[0279] (Raw material resin I)
[0280] Polypropylene, which is a propylene homopolymer obtained using a Ziegler-Natta catalyst, has an MFR of 60 g / 10 min, an Mw of 204987, an Mw / Mn of 7.98, an Mz / Mw of 5.11, a melting point of 160°C, and a branching degree λ of 1.0×10 -6 .
[0281] (Raw material resin J)
[0282] Polypropylene, which is a propylene homopolymer obtained by using a Ziegler-Natta catalyst, has an MFR of 230 g / 10 min, an Mw of 151,000, an Mw / Mn of 5.31, an Mz / Mw of 2.70, and a branching degree λ of 0.
[0283] (Raw material resin K)
[0284] Polypropylene, which is a propylene homopolymer obtained by using a Ziegler-Natta catalyst, has an MFR of 3.3 g / 10 min, an Mw of 575,000, an Mw / Mn of 6.69, an Mz / Mw of 3.20, and a degree of branching λ of 0.
[0285] (Polypropylene Masterbatch α)
[0286] "VMPP10X" manufactured by Polytechs (polypropylene masterbatch: containing 10% by mass of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane).
[0287] (Organic Peroxide β)
[0288] "PERHEXA 25B" manufactured by NOF Corporation (organic peroxide: 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane).
[0289] [Example 1]
[0290] (a) Step of obtaining polypropylene resin
[0291] For 100 parts by mass of the raw resin A, the crumbs were blended with 2.5 parts by mass of polypropylene masterbatch α. Then, the mixed crumbs were melt-extruded at 230°C by a single screw extruder, and the molten resin was supplied to the spinning spinneret while being metered by a gear pump. The obtained polypropylene resin had an MFR of 200 g / 10 min, an Mw of 132899, an Mw / Mn of 2.95, an Mz / Mw of 1.85, and a branching degree λ of 1.0×10 -6 .
[0292] (b) Process of obtaining fibers
[0293] Next, the spinning temperature (spinneret temperature) was set to 230° C., and the polypropylene resin was ejected from a spinneret having a hole diameter D of 0.30 mm and a molding section length L of 0.75 mm at a single hole ejection rate of 0.4 g / min. The following spinning spinneret was used, wherein the introduction hole located directly above the spinneret hole was a straight hole, and the connecting portion between the introduction hole and the spinneret hole was tapered.
[0294] In addition, the ejected fibrous resin was cooled and solidified by blowing cooling air at a temperature of 12° C. and a speed of 30 m / min from the outside, and then pulled by air flow at a spinning speed of 4.0 km / min using a rectangular ejector to obtain fibers. At this time, the distance from the spinneret of the spinning spinneret to the ejector inlet as the cooling start position was set to 550 mm.
[0295] (c) Fiber Capture Step
[0296] Next, the fibers obtained above were spread by passing through a spread portion where the air flow rate around them was reduced, and then landed on a net conveyor that sucked air from the back to collect them, thereby obtaining a fiber web. The fiber web was then conveyed at a speed of 11 m / min.
[0297] (d) Post-processing
[0298] Next, the fiber web obtained as described above was thermally bonded at 130°C using a pair of upper and lower heat embossing rolls, which consisted of an upper roll made of metal and having a water drop pattern engraved thereon and a bonding area ratio of 16% and a lower roll made of metal flat roll, to obtain a fiber web having a unit area weight of 30 g / m 2 Spunbond nonwoven fabric.
[0299] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 1. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 12.0 μm, and a tensile strength per unit area weight of 0.89 (N / 25 mm) / (g / m 2 ), stiffness is 1.6mN·cm, number of defects is 2, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0300] [Example 2]
[0301] In step (a), the raw material resin A was changed to raw material resin B, and in step (b), the spinning speed was changed from 4.0 km / min to 3.5 km / min. A spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209623, Mw / Mn was 2.97, Mz / Mw was 1.91, and the degree of branching λ was 1.0×10 -6 .
[0302] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 1. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 13.0 μm, and a tensile strength per unit area weight of 0.91 (N / 25 mm) / (g / m 2 ), stiffness is 1.8mN·cm, number of defects is 3, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0303] [Example 3]
[0304] A spunbonded nonwoven fabric was obtained by the same method as in Example 1 except that the raw material resin A was changed to the raw material resin C in step (a) and the spinning speed was changed from 4.0 km / min to 2.5 km / min in step (b). It should be noted that the MFR of the polypropylene resin obtained in step (a) was 20 g / 10 min, Mw was 299587, Mw / Mn was 2.98, Mz / Mw was 1.93, and the degree of branching λ was 1.0×10 -6 .
[0305] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 1. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 15.0 μm, and a tensile strength per unit area weight of 0.89 (N / 25 mm) / (g / m 2 ), stiffness is 2.0mN·cm, number of defects is 5, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0306] [Example 4]
[0307] A spunbonded nonwoven fabric was obtained by the same method as in Example 1 except that the raw material resin A was changed to the raw material resin D in step (a) and the spinning speed was changed from 4.0 km / min to 4.5 km / min in step (b). The MFR of the polypropylene resin obtained in step (a) was 380 g / 10 min, the Mw was 105955, the Mw / Mn was 2.92, the Mz / Mw was 1.83, and the degree of branching λ was 1.0×10-6 .
[0308] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 1. The average single fiber diameter of the obtained spunbonded nonwoven fabric was 11.2 μm, and the tensile strength per unit area weight of the spunbonded nonwoven fabric was 0.79 (N / 25 mm) / (g / m 2 ), stiffness is 1.2mN·cm, number of defects is 1, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0309] [Table 1]
[0310]
Table 1
[0311]
[0312] [Comparative Example 1]
[0313] A spunbonded nonwoven fabric was obtained by the same method as in Example 1 except that the raw material resin A was changed to the raw material resin E in step (a) and the spinning speed was changed from 4.0 km / min to 4.5 km / min in step (b). It should be noted that the MFR of the polypropylene resin obtained in step (a) was 500 g / 10 min, Mw was 96173, Mw / Mn was 2.90, Mz / Mw was 1.81, and the degree of branching λ was 1.0×10 -6 .
[0314] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 2. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 11.4 μm, and a tensile strength per unit area weight of 0.45 (N / 25 mm) / (g / m 2 ), stiffness was 0.9 mN·cm, number of defects was 1, and although the obtained nonwoven fabric had excellent softness and few defects, its mechanical properties were inferior to those of Example 1, and there were also problems with high-order processability.
[0315] [Comparative Example 2]
[0316] In step (a), the raw material resin A was changed to raw material resin F, and in step (b), the spinning speed was changed from 4.0 km / min to 2.0 km / min. A spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 10 g / 10 min, Mw was 382637, Mw / Mn was 3.00, Mz / Mw was 1.95, and the degree of branching λ was 1.0×10 -6 .
[0317] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 2. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 16.0 μm, and a tensile strength per unit area weight of 0.70 (N / 25 mm) / (g / m 2 ), stiffness is 3.5 mN·cm, number of defects is more than 20, and the obtained nonwoven fabric has excellent mechanical properties and no problem in high-order processability, but poor softness and many defects.
[0318] [Example 5]
[0319] In step (a), 2.5 parts by mass of polypropylene masterbatch α was blended with 100 parts by mass of raw resin A, whereas 0.25 parts by mass of organic peroxide β was blended with 100 parts by mass of raw resin B, and in step (b), the spinning speed was changed from 4.0 km / min to 3.5 km / min. A spunbonded nonwoven fabric was obtained by the same method as in Example 1. The polypropylene resin obtained in step (a) had an MFR of 55 g / 10 min, an Mw of 209623, an Mw / Mn of 2.97, an Mz / Mw of 1.91, and a branching degree λ of 1.0×10 -6 .
[0320] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 2. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 13.0 μm, and a tensile strength per unit area weight of 0.87 (N / 25 mm) / (g / m 2 ), stiffness is 1.8mN·cm, number of defects is 3, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0321] [Example 6]
[0322] In step (a), the temperature during melt extrusion was 230°C, but was changed to 200°C. A spunbonded nonwoven fabric was obtained by the same method as in Example 2. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209623, Mw / Mn was 2.97, Mz / Mw was 1.96, and the degree of branching λ was 1.0×10 -6 .
[0323] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 2. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 13.0 μm, and a tensile strength per unit area weight of 0.93 (N / 25 mm) / (g / m 2), stiffness is 1.8mN·cm, number of defects is 2, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0324] [Table 2]
[0325]
Table 2
[0326]
[0327] [Example 7]
[0328] In step (a), the raw material resin A was changed to raw material resin G, and in step (b), the spinning speed was changed from 4.0 km / min to 1.5 km / min. A spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209623, Mw / Mn was 2.97, Mz / Mw was 1.91, and the degree of branching λ was 1.0×10 -5 .
[0329] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 3. The average single fiber diameter of the obtained spunbonded nonwoven fabric was 16.4 μm, and the tensile strength per unit area weight of the spunbonded nonwoven fabric was 0.71 (N / 25 mm) / (g / m 2 ), stiffness is 1.8mN·cm, number of defects is 8, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0330] [Example 8]
[0331] A spunbonded nonwoven fabric was obtained by the same method as in Example 1 except that the raw material resin A was changed to the raw material resin H in step (a) and the spinning speed was changed from 4.0 km / min to 3.5 km / min in step (b). It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209623, Mw / Mn was 2.96, Mz / Mw was 1.91, and the degree of branching λ was 1.0×10 -7 .
[0332] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 3. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 13.0 μm, and a tensile strength per unit area weight of 0.85 (N / 25 mm) / (g / m 2 ), stiffness is 3.0mN·cm, number of defects is 3, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0333] [Comparative Example 3]
[0334] In step (a), the raw material resin A was changed to raw material resin I, and the polypropylene masterbatch α was not used (no organic peroxide was added). In step (b), the spinning speed was changed from 4.0 km / min to 3.5 km / min. A spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209623, Mw / Mn was 3.22, Mz / Mw was 2.36, and the degree of branching λ was 1.0×10 -6 .
[0335] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 3. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 13.0 μm, and a tensile strength per unit area weight of 0.52 (N / 25 mm) / (g / m 2 ), stiffness is 1.8 mN·cm, number of defects is 3, although the obtained nonwoven fabric has excellent softness and few defects, its mechanical properties are worse than those of Example 2, and there are problems with high-order processability.
[0336] [Comparative Example 4]
[0337] In step (a), the temperature during melt extrusion was 230°C, but was changed to 180°C. A spunbonded nonwoven fabric was obtained by the same method as in Example 2. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209623, Mw / Mn was 2.97, Mz / Mw was 1.96, and the degree of branching λ was 1.0×10 -6 .
[0338] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 3. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 13.0 μm, and a tensile strength per unit area weight of 0.89 (N / 25 mm) / (g / m 2 ), stiffness was 1.6 mN·cm, number of defects was 3, and the obtained nonwoven fabric had not only softness but also excellent mechanical properties, few defects, and no problems with high-order processing. However, in terms of the effect on the skin, in the evaluation using a human epidermis model assumed to be sensitive skin, the cell survival rate after culture was less than 95%.
[0339] [Table 3]
[0340]
Table 3
[0341]
[0342] [Comparative Example 5]
[0343] In step (a), the raw material resin A was changed to raw material resin J, and the polypropylene masterbatch α was not used (no organic peroxide was added), and in step (b), the spinning speed was changed from 4.0 km / min to 4.2 km / min, and a spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 230 g / 10 min, Mw was 151000, Mw / Mn was 5.31, Mz / Mw was 2.70, and the degree of branching λ was 0.
[0344] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 4. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 11.7 μm, and a tensile strength per unit area weight of 0.90 (N / 25 mm) / (g / m 2 ), stiffness was 0.8 mN·cm, and the number of defects was 1. Although the obtained nonwoven fabric had excellent mechanical properties and few defects, there were problems with high-order processability.
[0345] [Example 9]
[0346] In step (a), 2.5 parts by mass of polypropylene masterbatch α was blended with 100 parts by mass of raw resin A, but 1.1 parts by mass of the masterbatch was blended with the masterbatch, and in step (b), the spinning speed was changed from 4.0 km / min to 3.5 km / min. A spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 55 g / 10 min, Mw was 209000, Mw / Mn was 3.71, Mz / Mw was 2.26, and the degree of branching λ was 5.0×10 -7 .
[0347] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 4. The average single fiber diameter of the obtained spunbonded nonwoven fabric was 12.8 μm, and the tensile strength per unit area weight of the spunbonded nonwoven fabric was 0.90 (N / 25 mm) / (g / m 2 ), stiffness is 2.0mN·cm, number of defects is 3, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0348] [Example 10]
[0349] In step (a), 2.5 parts by mass of polypropylene masterbatch α was blended with 100 parts by mass of raw resin A, and 3.5 parts by mass of the masterbatch was blended with the masterbatch. A spunbonded nonwoven fabric was obtained by the same method as in Example 1 except that the masterbatch was blended with 3.5 parts by mass. The polypropylene resin obtained in step (a) had an MFR of 380 g / 10 min, an Mw of 105,000, an Mw / Mn of 2.80, an Mz / Mw of 1.80, and a degree of branching λ of 5.0×10 -5 .
[0350] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 4. The average single fiber diameter of the obtained spunbonded nonwoven fabric was 12.0 μm, and the tensile strength per unit area weight of the spunbonded nonwoven fabric was 0.85 (N / 25 mm) / (g / m 2 ), stiffness is 1.5mN·cm, number of defects is 2, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0351] [Comparative Example 6]
[0352] In step (a), raw material resin A was changed to raw material resin K, and in step (b), the spinning speed was changed from 4.0 km / min to 3.6 km / min, and a spunbonded nonwoven fabric was obtained by the same method as in Example 1. The polypropylene resin obtained in step (a) had an MFR of 220 g / 10 min, an Mw of 147,000, an Mw / Mn of 2.96, an Mz / Mw of 1.91, and a degree of branching λ of 0.
[0353] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 4. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 12.5 μm, and a tensile strength per unit area weight of 0.90 (N / 25 mm) / (g / m 2 ), stiffness was 0.7 mN·cm, and the number of defects was 1. Although the obtained nonwoven fabric had excellent mechanical properties and few defects, there were problems with high-order processability.
[0354] [Table 4]
[0355]
Table 4
[0356]
[0357] [Example 11]
[0358] In step (c), the bonding temperature by the hot embossing roll was changed from 130°C to 135°C, and a spunbonded nonwoven fabric was obtained by the same method as in Example 1. It should be noted that the MFR of the polypropylene resin obtained in step (a) was 200 g / 10 min, Mw was 132899, Mw / Mn was 2.95, Mz / Mw was 1.85, and the degree of branching λ was 1.0×10 -6 .
[0359] The evaluation results of the obtained spunbonded nonwoven fabric are shown in Table 5. The obtained spunbonded nonwoven fabric had an average single fiber diameter of 12.0 μm, and a tensile strength per unit area weight of 1.09 (N / 25 mm) / (g / m 2 ), stiffness is 1.9 mN·cm, number of defects is 2, the obtained nonwoven fabric is not only soft but also has excellent mechanical properties, few defects, and no problem with high-order processability.
[0360] [Table 5]
[0361]
Table 5
[0362]
Claims
1. A spunbonded nonwoven fabric, which is a spunbonded nonwoven fabric composed of fibers formed from a polypropylene resin, wherein: The spunbonded nonwoven fabric satisfies the following conditions (1) to (3), and the average single fiber diameter of the fibers is 5.0 μm or more and 20.0 μm or less, (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 15 minutes, 45 kHz, and a solution temperature of 30° C., and the amount of organic peroxide extracted is 100 ppm or more and 1000 ppm or less; (2) The melt flow rate is 20 g / 10 min to 400 g / 10 min; (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
2. The spunbonded nonwoven fabric according to claim 1, wherein: The polypropylene resin further satisfies the following conditions (4) and (5), (4) 2.50≤Mw / Mn≤3.20; (5)1.82≤Mz / Mw≤2.20 Here, Mw, Mn, and Mz are weight average molecular weight, number average molecular weight, and z average molecular weight respectively determined by gel permeation chromatography.
3. The method for producing a spunbonded nonwoven fabric according to claim 1 or 2, comprising: A step of adding an organic peroxide to a raw material resin to decompose the raw material resin to obtain a polypropylene-based resin prepared so as to satisfy the following conditions (1) to (3); The step of spinning the polypropylene resin to obtain fibers having an average single fiber diameter of 5.0 μm to 20.0 μm; and a step of capturing the fibers, (1) the spunbonded nonwoven fabric immersed in a chloroform / methanol solvent having a volume ratio of 1:1 is ultrasonically treated under conditions of 15 minutes, 45 kHz, and a solution temperature of 30° C., and the amount of organic peroxide extracted is 100 ppm or more and 1000 ppm or less; (2) The melt flow rate is 20 g / 10 min to 400 g / 10 min; (3) The branching degree λ per molecule of the polypropylene resin calculated using the trifunctional random branching theory using the molecular weight and gyration radius determined by gel permeation chromatography / multi-angle light scattering measurement device is 1.0×10 -7 Above 1.0×10 -3 the following.
4. The method for producing a spunbonded nonwoven fabric according to claim 3, wherein: The raw material resin is a recycled resin.
5. A laminated nonwoven fabric comprising the spunbonded nonwoven fabric according to claim 1.
6. A sanitary material comprising the spunbonded nonwoven fabric according to claim 1 or the laminated nonwoven fabric according to claim 5.
7. Clothing made of the spunbonded nonwoven fabric according to claim 1 or the laminated nonwoven fabric according to claim 5.
Citation Information
Patent Citations
Non-woven web with improved barrier characteristics
JP1995119014A
Organic peroxide-containing polypropylene-based resin composition and molded product using the same
JP2003138075A
New bicomponent fiber
CN102791913A
Polypropylene non-woven fabric and making method thereof
CN104250883A
Polypropylene resin suitable for fibers and nonwovens
CN1918228A